2008
DOI: 10.1002/ps.1587
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key climatic factors regulating the transport of pesticides in leaching and to tile drains

Abstract: Numerous climatic characteristics influenced pesticide loss, including the amount of precipitation as well as the timing of rainfall and extreme events in relation to application date. Information regarding the relative influence of the climatic characteristics evaluated here can support the development of a climatic zonation for European-scale risk assessment for pesticide fate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 26 publications
(29 reference statements)
1
25
0
4
Order By: Relevance
“…If, for example, geochemical processes such as pollutant mobilisation are an overwhelming concern, sensitivity studies can be conducted to identify Nolan et al, 2008). In this paper the processes of interest are river flows from mountainous headwaters and agricultural production, both of which depend upon inputs of mass (precipitation) and energy (ambient temperature and incoming radiation).…”
Section: Selection Of Climate Variables Governing Water Resources Andmentioning
confidence: 99%
“…If, for example, geochemical processes such as pollutant mobilisation are an overwhelming concern, sensitivity studies can be conducted to identify Nolan et al, 2008). In this paper the processes of interest are river flows from mountainous headwaters and agricultural production, both of which depend upon inputs of mass (precipitation) and energy (ambient temperature and incoming radiation).…”
Section: Selection Of Climate Variables Governing Water Resources Andmentioning
confidence: 99%
“…포아송 클러스터 강우생성 모형은 기존의 자 기 상관성에 기반을 둔 모형과 비교하였을 때, (1) 넓은 시간대(1시간-1개월)에 대하여 관측강우의 통계치를 재 현할 수 있으며, (2) 세밀한 시간 해상도(1시간 단위)를 가 진 강우시계열의 생성이 가능하고, (3) 극한값들을 잘 재 현한다는 강점을 가지고 있다 . 이러 한 모형의 장점으로 인하여, 포아송 클러스터 강우생성 모형은 도시지역에서의 홍수 (Moretti and Montanari, 2004;Brath et al, 2006, Dawson et al, 2006, 농약의 확 산 (Nolan et al, 2008), 산사태 (Bathurst et al, 2005), 사막 화 (Bathurst and Bovolo, 2004), 수자원 평가 (Fowler et al, 2005), 홍수위험도 평가 (Kilsby et al, 2000) (1)…”
Section: Fig 1 the Concept Of Poisson Cluster Rainfall Generation Munclassified
“…Capel et al, 2001;Holvoet et al, 2007;Nolan et al, 2008;Lewan et al, 2009). In a lysimeter study, Beulke et al (2002) found an exponential relationship between pesticide losses and total outflow for soils susceptible to preferential flow.…”
Section: Introductionmentioning
confidence: 99%